(-4/3)x(1/5)=-5

Simple and best practice solution for (-4/3)x(1/5)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-4/3)x(1/5)=-5 equation:


(-4/3)x(1/5)=-5

We simplify the equation to the form, which is simple to understand
(-4/3)x(1/5)=-5

Simplifying:
(-1.33333333333)*x*(1/5)=-5

Simplifying:
(-1.33333333333)*x*( + 0.2)=-5

Reorder the terms in parentheses
(-1.33333333333x)*( + 0.2)=-5

Reorder the terms in parentheses
multiplication of parentheses
(-0.266666666666x)=-5



Remove unnecessary parentheses
-0.266666666666x=-5

We move all terms containing x to the left and all other terms to the right.
-0.266666666666x=-5

We simplify left and right side of the equation.
-0.266666666666x=-5

We divide both sides of the equation by -0.266666666666 to get x.
x=18.75

See similar equations:

| (49x^4y^6z^10)^(1/2) | | 6x+12=3x+21 | | (-8)(-4)(0)= | | 4x=-25-6x | | 1.4+(0.9)= | | x-2/4=5 | | y^3+4y^2+6y+4=0 | | 3(5x-10)=20x | | 2x=-7x+18 | | 12y-18x=18 | | 10n=7n+7+2n | | 9x-(3*7)=6 | | 5000x=250+20x | | y^2+14y+27=0 | | 7-2(f+3)=2(4-3f) | | -2x+7=28 | | 3(8-5)-3(16+12)= | | X-4-3x=-2x+5-1 | | 4x-21+7x-3=9x-11+3x | | 6u^2-u-1=0 | | 6p+13=31 | | 3x+12y=51 | | 5m+12+2m=2m+18-5 | | -4.9+x=11.3 | | (6x-11)/2x | | 4a-(a-2)=19+3a | | -12x+3x-202=59 | | 6+4a=16+2a | | 20=5y/7 | | -(5x-5)= | | -113+5x+10x=97 | | 5-(h+3)=-1+2(h-3) |

Equations solver categories